2020
DOI: 10.2139/ssrn.3805685
|View full text |Cite
|
Sign up to set email alerts
|

Still the Lands of Equality? On the Heterogeneity of Individual Factor Income Shares in the Nordics

Abstract: As far as standard measures of income inequality are concerned, the Nordic countries rank among the most equal economies in the world. This paper studies whether and how this picture changes when the focus is on inequality of income composition, meaning the heterogeneity in individuals' factor income shares. We highlight the structural change taking place in all the Nordic countries since the early 1990s, with rising inequality in composition of individual incomes due mostly to a shift in capital incomes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Fochesato and Bowles (2015) similarly argue that "Nordic exceptionalism" is not due to exceptional equality in wealth, but to high social mobility and low inequality of earnings. Iacono and Palagi (2020) have documented the recent rise in compositional inequality in the Nordic countries, and claim that this was helped by the emergence of Dual Income Tax (DIT) reforms in the early 1990s, characterized by a flat tax on capital incomes (which is considerably lower than the tax rate on labor incomes). Additionally, both Sweden (in 2004) and Norway (in 2014) have abolished taxation of inheritance.…”
Section: Much Higher Concentration Of Capital Income Among Nordic Countries Canmentioning
confidence: 99%
“…Fochesato and Bowles (2015) similarly argue that "Nordic exceptionalism" is not due to exceptional equality in wealth, but to high social mobility and low inequality of earnings. Iacono and Palagi (2020) have documented the recent rise in compositional inequality in the Nordic countries, and claim that this was helped by the emergence of Dual Income Tax (DIT) reforms in the early 1990s, characterized by a flat tax on capital incomes (which is considerably lower than the tax rate on labor incomes). Additionally, both Sweden (in 2004) and Norway (in 2014) have abolished taxation of inheritance.…”
Section: Much Higher Concentration Of Capital Income Among Nordic Countries Canmentioning
confidence: 99%
“…The 1990s saw a range of tax reforms in the Nordic region. The introduction of dualincome taxation, lowering the degree of progressivity in capital income taxation, the reductions in top marginal tax rates, and the general lowering of capital taxation in the Nordic countries -from between 50-60 per cent to between 20-30 per cent (2020)resulted in an increasing accumulation of capital incomes towards the top of the income distribution (Iacono & Palagi, 2020). The fact that the rich have become richer has been further spurred by inheritance tax being abolished (in Sweden and Norway), real estate tax being repealed (in Sweden, although it has been retained in the other Nordic countries), and corporate tax being reduced to a level far below the postwar period.…”
Section: Class and The Nordic Countriesmentioning
confidence: 99%
“…The second type is heterogeneity in the distribution of capital and labor incomes across the income distribution. Recent studies have shown that, globally, poor individuals derive most of their income from labor, whilst rich individuals derive most of their income from capital (Ranaldi and Milanovic, 2022, Iacono and Palagi, 2022b, Iacono and Ranaldi, 2022. We call this type of heterogeneity endowment heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…As for behavioral heterogeneity, seeDynan et al (2004),Saez and Zucman (2016),Jappelli and Pistaferri (2014),Bunn et al (2018) among others, whilst for endowment heterogeneity, seeRanaldi and Milanovic (2022),Iacono and Ranaldi (2022),Iacono and Palagi (2022b),Petrova and Ranaldi (2021),Berman and Milanovic (2020).…”
mentioning
confidence: 99%